INFLUENCE OF SOCIAL SUPPORT FOR FAMILIES PARENTING MOTHER IN PREVENTING CHILD STUNTING - Setyawan Yulian Nugraha; Nur Fatikhah; Sulis Tri Wahyuni; Noer Saudah (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2019)
Stunting was one form of malnutrition characterized by height does not correspond to the age. The occurrence of stunting very influenced by parenting in providing nutrition in children toddlers. The purpose of this study was to analyze the relationship of social support to parenting mother's family in toddlers in the village Jabon subdistrict Mojoanyar Mojokerto regency. The method used correlation analytic design with cross sectional. The study population is the mother of the toddler who is housed in villages Jabon subdistrict Mojoanyar Mojokerto district with lots of 250 children. The sample size were 70 samples used by simple random sampling. Analysis data used linear regression. Variabel independent was social supportand was parenting mother's family. Instrumen used questionnaire social support the family with good frequency rate by 35 respondents (50.0%). Maternal parenting in preventing stunting in children with good frequency rate by 37 respondents (52.9%). Results of linear regression test with p equal to 0.00. This means relationship between social support to parenting mother's family in toddlers. The better social support mother's family then parenting in toddlers the better so as to prevent stunting.